Comparison of IgA, TNF-α and surface tension of the tear film in two different times of the day - Puinhas, Ana; Sampaio, Paula; Castanheira, Elisabete M.S.; Real Oliveira, M. Elisabete C.D.; Lira, Madalena (Contact lens & anterior eye, 2013)
The main goal was to study the biochemical composition of the tear film in two different times of the day. Tear samples were collected from 10 individuals, non contact lenses wearers, from the university population without pathologies. To assess daily variations in the tear film, samples were collected twice in the day, one early in the morning and another in the evening using capillary tubes. Tear protein profile was analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), tumor necrosis factor α (TNF-α) and immunoglobulin A (IgA) were quantified by Enzyme-Linked ImmunoSorbent Assay (ELISA). Tear film stability was obtained through measurements of Non-Invasive Break Up Time and tear surface tension was measured by obtaining the Langmuir isotherms. The stability of the tear film was higher in the morning than in the afternoon; corresponding to a higher value of surface tension in the afternoon. Protein electrophoresis tear profile is variable during the day as IgA concentration decreased from morning to afternoon (p<0.05). TNF-α concentration also decreased, but there were not significant statistical differences (p=0.089). We concluded that there are daily variations in the composition and properties of the tear film, indicating that changes occur without being caused by contact lenses wear or by the presence of ocular and systemic pathologies. Presence of TNF-α is not a direct indication of inflammatory pathology, since this cytokine was identified in relatively high amounts in subjects without inflammatory pathology.